Kadar Mineral Tembaga dan Besi Dalam Bulu Serta Kaitannya Dengan Kasus Anemia Pada Kambing - Sugito Sugito (Agricultural Faculty, 2008)
Mineral content of Cu and Fe in plasma and hair in related to anemia cases on female goatABSTRACT. A research had been done to identify mineral content of Cu and Fe in plasma and hair related to anemia case on female goat. Twenty female local goats at the age of 12-16 months taken from Kecamatan Darussalam and Kecamatan Baitussalam Kabupaten Aceh Besar were applied. The goats taken have the criteria of hemoglobin rate (Hb) and/or Packed Cell Volume (PCV) lower than normal level. Hair and blood were sampled in this research. Hair samples were taken from top tail area, while blood samples were taken from jugular vein. The result indicated that the average rate of Hb was 77 0.7 mg/dl and PCV was 191 1.3%. The average rate of Cu and Fe in plasma was 0.7 0.16 and 67.8 10.3 g/ml, while in hair was 2.40 0.511 and 315 8.4 g/g. The average rate of Cu in plasma was categorized as below normal, while the average rate of Fe in the range of marginal. Regression analysis showed that there was close correlation between Hb rates and PCV as well as the correlation of Hb rate and Cu rate in hair. However, there was no close correlation between Hb rate and Fe rate in hair. The conclusion of the research implied that the amount of PCV and Cu rate in hair relevant to the Hb rate in blood, and could subsequently predict anemia case occurring on female goats.